The Effects of Lysophosphatidic Acid on The Incidence of Cell Death in Cultured Vitrified and Non-Vitrified Mouse Ovarian Tissue: Separation of Necrosis and Apoptosis Border - Abedpour, Neda (Cell J, 2018)
OBJECTIVE: The aim of the present study was to examine whether lysophosphatidic acid (LPA) could decrease cell death and improve in vitro culture (IVC) conditions in cultured vitrified mouse ovarian tissue. MATERIALS AND METHODS: In this experimental study, we collected and randomly divided 7-day-old mouse ovarian tissues into vitrified and non-vitrified groups. The ovaries were cultured in the presence and absence of LPA for one week. Morphology and follicular development were evaluated by hematoxylin and eosin (H&E) and Masson’s trichrome (MTC) staining. The incidence of cell death was assessed by flow cytometry using annexin V/propidium iodide (PI) and a caspase-3/7 assay in all studied groups. RESULTS: The vitrified groups had a significantly decreased follicle developmental rate compared to the non-vitrified groups (P<0.05). Overall, qualitative and quantitative results showed prominent follicular degeneration in the vitrified groups compared with the respective non-vitrified groups. Both LPA treated groups had a significantly higher proportion of preantral follicles compared to the non-LPA treated groups (P<0.05). Flow cytometry analysis results showed significantly greater early and late apoptotic cells in all groups (17.83 ± 8.80%) compared to necrotic cells (7.97 ± 0.92%, P<0.05). The percentage of these cells significantly increased in the vitrified groups compared with non-vitrified groups. LPA treated groups had a lower percentage of these cells compared to non-LPA treated groups (P<0.05). The lower enzyme activity was observed in non-vitrified (especially in the LPA(+) groups) cultured ovaries compared to the vitrified group (P<0.05). CONCLUSION: Both vitrification and IVC adversely affected cell survival and caused cell death. We postulated that LPA supplementation of culture medium could improve the developmental rate of follicles and act as an anti-cell death factor in non-vitrified and vitrified ovarian tissues. It could be used for in vitro maturation of ovarian tissue.